Pengaruh Sikap Sosial Siswa Terhadap Hasil Belajar Mata Pelajaran PPKN Siswa Kelas VIII DI SMP Negeri 6 Kerinci - Mufti, Ansari; Sutja, Akmal; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2023)
This research was conducted at SMP Negeri 6 Kerinci in the even semester of the 2021/2022 academic year. In the initial observation, the researchers found that the learning outcomes of PPKn for some students were still below the KKM. This study aims to determine the effect and magnitude of the influence of students' social attitudes on the learning outcomes of PPKN subjects for class VIII students at SMP Negeri 6 Kerinci. The research method in this study is quantitative. In connection with this study, the approach used by researchers is the Ex Post Facto approach. As for data collection techniques, namely interviews and questionnaires. Based on the results of the data analysis that has been carried out, it can be concluded that the variable social attitudes of students (X) has a significant effect on the learning outcome variable (Y) for PPKN subjects for class VIII students at SMP Negeri 6 Kerinci. This is evidenced by the value of tcount > ttable (2.081> 1.99254) and a significant value of 0.041 <0.05 with the intention that social attitudes have a significant impact on the learning outcomes of Civics class VIII students at SMP Negeri 6 Kerinci. The magnitude of the influence can be seen on the Coefficient of Determination, which is obtained R2 = 0.055, which is percentaged to 5.5%. So the big influence is 5.5% while the remaining 94.5% is influenced by other variables not examined in this research.